2008
DOI: 10.1093/carcin/bgn036
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of acetylcholinesterase with caveolin-1 and subsequently with cytochrome c are required for apoptosome formation

Abstract: Acetylcholinesterase (AChE) is emerging as an important component in leading to apoptosis. Our previous study demonstrated that silencing of the AChE gene blocked the interaction between cytochrome c and apoptotic protease-activating factor-1 (Apaf-1) in etoposide-induced apoptosis of HT-29 cells. We undertook this study to further dissect the molecular role of AChE in apoptosome formation. The present study elicited that small interfering RNA (siRNA) to cytochrome c gene blocked the interaction of AChE with A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 28 publications
1
33
0
1
Order By: Relevance
“…Our data partially consistent with previous reports that AChE is required for apoptosome formation [31]. Other researches indicated that ACh stimulated the nicotinic acetylcholine receptor (nAChR) signaling which is pathologically over-activated in tumor [1].…”
Section: Discussionsupporting
confidence: 93%
“…Our data partially consistent with previous reports that AChE is required for apoptosome formation [31]. Other researches indicated that ACh stimulated the nicotinic acetylcholine receptor (nAChR) signaling which is pathologically over-activated in tumor [1].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, AChE interacts with Caveolin-1 during apoptosis in events that precede apoptosome formation. While AChE plays a crucial role in promoting oligomerization of Apaf-1, Caveolin-1 appears neither to interact with cytochrome C nor with Apaf-1 [110].…”
Section: Caveolin-1 and Apoptosismentioning
confidence: 95%
“…In a non-synaptic context, the reports dealing with the altered expression of AChE in a wide range of tumor classes [13], along with the well-documented capacity of AChE to halt the cell cycle progression [14] and to promote apoptosis by facilitating the apoptosome assembly [15][16][17] raise the possibility that AChE collaborate to carcinogenesis through different pathways. The reports showing that AChE functions as a tumor growth suppressor in hepatocellular carcinoma [18,19] and in non-small cell lung cancer, in the latter via suppression by an AChE-targeted microRNA-212 [20] lend strong support to the relationship of AChE with tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%